2015
DOI: 10.3126/kumj.v13i1.13749
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Sociodemographics and Personal Hygiene on Different Childhood Dermatoses

Abstract: BackgroundSkin diseases in children contribute to significant morbidity and psychological distress. Infective dermatoses are one of the major dermatoses in children. Low socioeconomic status, overcrowding and poor personal hygiene has been linked to skin diseases. ObjectiveTo find out the prevalence of infectious skin disease in children, rate of transmissible skin disease and association of sociodemographic factors and personal hygiene on infective childhood dermatoses. MethodThis was a cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 9 publications
6
14
2
2
Order By: Relevance
“…With regards to aetiologic categories of skin diseases, infective skin diseases were the predominant lesion encountered in this study. A similar finding has been reported in several other studies [10,[20][21][22]. It could be inferred that these infective skin diseases predominate in resource limited settings like ours because of the prevailing overcrowding and poor sanitary conditions that promote the breeding of pathogens implicated in the aetiology of these infective skin diseases.…”
Section: Discussionsupporting
confidence: 91%
“…With regards to aetiologic categories of skin diseases, infective skin diseases were the predominant lesion encountered in this study. A similar finding has been reported in several other studies [10,[20][21][22]. It could be inferred that these infective skin diseases predominate in resource limited settings like ours because of the prevailing overcrowding and poor sanitary conditions that promote the breeding of pathogens implicated in the aetiology of these infective skin diseases.…”
Section: Discussionsupporting
confidence: 91%
“…This is because, these items can serve as fomites harboring and transmitting the micro-organisms responsible for these skin diseases from one person to another. Gauchan et al [9] reported a similar finding in a study done in Nepal. Our study may have been limited by the relatively short duration covered as a longer duration would have allowed for a larger sampling frame to be generated.…”
Section: Discussionsupporting
confidence: 63%
“…In a study done in Nepal, Gauchan et al [9], reported factors associated with skin diseases especially infections and infestations to include: low socio-economic status, overcrowding, sharing of common bath items and less frequent baths (<1 /week).…”
Section: Introductionmentioning
confidence: 99%
“…Penerapan kebersihan pribadi maka dapat memutuskan mata rantai penularan agen penyebab penyakit kulit dari tempat hidupnya ke host. Penyakit kulit akan lebih mudah menyerang apabila imun seseorang turun 7 .…”
Section: Bahan Dan Caraunclassified